H_{2} adsorption on multiwalled carbon nanotubes at low temperatures and low pressures - F. Xu (Physical Review Special Topics. Accelerators and Beams, 2008)
We present an experimental study on H_{2} adsorption on multiwalled carbon nanotubes (MWCNTs) at low temperatures (12–30 K) and low pressures (2×10^{-5}  Torr) using the temperature programmed desorption technique. Our results show that the molecular hydrogen uptake increases nearly exponentially from 6×10^{-9}  wt. % at 24.5 K to 2×10^{-7}  wt. % at 12.5 K and that the desorption kinetics is of the first order. Comparative measurements indicate that MWCNTs have an adsorption capacity about two orders higher than that of activated carbon (charcoal) making them a possible candidate as hydrogen cryosorber for eventual applications in accelerators and synchrotrons.